The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1080/13607863.2020.1725738
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of dementia amongst the general public across Latin America: a systematic review

Abstract: Perceptions of dementia amongst the general public across Latin America: a systematic review. Aging and Mental Health. pp. 1-10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 49 publications
2
22
0
3
Order By: Relevance
“…Awareness and Stigma ( Priority Rating: 23.7%, Time window: next 0‐5 years ). Low awareness and stigma have proved a barrier to early characterization of dementia 1,25,26,70–72 . Both factors are pervasive in LACs 73 .…”
Section: Knowledge Creationmentioning
confidence: 99%
See 1 more Smart Citation
“…Awareness and Stigma ( Priority Rating: 23.7%, Time window: next 0‐5 years ). Low awareness and stigma have proved a barrier to early characterization of dementia 1,25,26,70–72 . Both factors are pervasive in LACs 73 .…”
Section: Knowledge Creationmentioning
confidence: 99%
“…1,25,26,[70][71][72] Both factors are pervasive in LACs. 73 Senior Latinos find it difficult to talk about cognitive evaluation because discussing cognitive and mental health is considered a taboo. 74 Messages used to promote awareness are often found to be vague and produce feelings of guilt.…”
Section: Epidemiological and Genetic Studiesmentioning
confidence: 99%
“…Moreover, high levels of stigma and discrimination towards psychiatrists and patients with dementia and other types of mental and neurological conditions (Gaebel et al, 2015;Ndetei, Ngumi, Zipporah, Mutiso, Musyimi, & Kamau, 2013) may also contribute to uncoordinated pathways to dementia care. These low levels of resources and negative perceptions can have profound effects on the person with dementia and their carers leading to depression, social isolation, loneliness, diminished quality of care and reduced health-care seeking (Farina, Suemoto, Burton, Oliveira, & Frost, 2020;Tan, Yeo, Koh, Wong, & Lee, 2020). "…”
Section: Introductionmentioning
confidence: 99%
“…Although information about cognitive impairment has been widely disseminated through numerous awareness campaigns and educational programs, several studies have revealed different gaps in the public's knowledge regarding dementia and AD [3][4][5][6]. Adequate AD knowledge throughout society could lead to earlier identification of this disorder in the population, which would result in earlier appropriate healthcare for people with dementia and would decrease the stigma associated with AD [3].…”
Section: Introductionmentioning
confidence: 99%